Adverse metabolic phenotype of adolescent girls with non‐alcoholic fatty liver disease plus polycystic ovary syndrome compared with other girls and boys. Issue 5 (May 2016) - Ayonrinde, Oyekoya T; Adams, Leon A; Doherty, Dorota A; Mori, Trevor A; Beilin, Lawrence J; Oddy, Wendy H; Hickey, Martha; Sloboda, Deborah M; Olynyk, John K; Hart, Roger
Abstract: Background and Aims: Non‐alcoholic fatty liver disease (NAFLD) and polycystic ovary syndrome (PCOS) share risk associations of adiposity and insulin resistance. We examined the impact of a PCOS diagnosis on the metabolic phenotype of adolescent girls with NAFLD and compared this to girls without PCOS or NAFLD and to age‐matched boys. Methods: Community‐based adolescents from the Raine Cohort participated in assessments for NAFLD (572 girls and 592 boys) and PCOS (244 girls). One hundred and ninety‐nine girls attended both assessments. Results: Amongst the 199 girls, PCOS was diagnosed in 16.1% and NAFLD in 18.6%. NAFLD was diagnosed in 10.1% of the boys. NAFLD was more prevalent in girls with PCOS than girls without PCOS (37.5% vs 15.1%, P = 0.003). Girls with NAFLD plus PCOS had greater adiposity (waist circumference, body mass index, suprailiac skinfold thickness [SST], serum androgens, high‐sensitivity C‐reactive protein, ferritin, homeostasis model assessment for insulin resistance (HOMA‐IR), and lower serum sex hormone binding globulin levels than girls with NAFLD without a PCOS diagnosis (all P < 0.05). Girls with NAFLD plus PCOS had similar adiposity, HOMA‐IR, and adiponectin levels to boys with NAFLD, but more adiposity, serum leptin and HOMA‐IR than both girls and boys without NAFLD. PCOS (odds ratios 2.99, 95% confidence intervals 1.01–8.82, P = 0.048) and SST (odds ratios 1.14, 95% confidence intervals 1.08–1.20, P < 0.001) independently predicted NAFLD in adolescent girls, however, serum androgens and HOMA‐IR levels did not. Conclusions: Adolescent girls with NAFLD plus PCOS have a similar metabolic phenotype to boys with NAFLD. Increasing SST and pre‐existing PCOS independently predict NAFLD in adolescent girls.